ANALISIS TOKOH DAN PENOKOHAN DALAM NOVEL TRILOGI RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Endah Febrianti; Wikanengsih Wikanengsih; Agus Priyanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research, entitled Analysis of the Main Character in the Novel "Ronggeng Dukuh Paruk" by Ahmad Tohari, was motivated by the emergence of social criticism. This study aims to analyze the main character in the novel Ronggeng Dukuh Paruk by Ahmad Tohari. The life in a dukuh is different from other villages which affects the character of its inhabitants. The method used is descriptive qualitative analysis. Data retrieval is done by reading, analyzing and marking the text or sentence included in the character and characterization so that it is easy to study, with this study the reader can take the good side of several figures to be implemented in social life, namely someone who is brave, compassionate, cares about others. . Even though living in a dukuh which is shrouded in poverty and ignorance, it is not as bad as others see it, although according to people their life is lacking but it does not make them complain all the time. The result of this research is that there are social conflicts that arise in the plot related to the characters and characterizations in the novel. Ahmad Tohari, as the author of the novel, describes the character of each character well and precisely so that readers can easily understand the plot and convey it successfully to the reader.Keywords: Ronggeng Dukuh Paruk, Figures, Characterizations.